Psychosocial predictors of HIV treatment outcomes among young pregnant and postpartum women living with HIV - Noholoza, Sandisiwe (Department of Public Health and Family Medicine, 2023)
Introduction: Young pregnant and postpartum women's suboptimum antiretroviral therapy (ART) adherence and engagement in HIV care remains a global concern despite improvements in prevention of mother-to-child transmission (PMTCT) and general ART services. Various psychosocial risk factors have been individually shown to be associated with HIV infection. However, longitudinal, and quantitative research on the impact of these psychosocial risk factors on HIV treatment outcomes is limited, particularly among young pregnant and postpartum women living with HIV (WLHIV) in low-income countries like South Africa. Furthermore, knowledge on the cumulative impact of these often-co-occurring psychosocial risk factors on HIV treatment outcomes is limited. This analysis examined the prevalence and co-occurrence of four key psychosocial risk factors [unintended pregnancy, depression, hazardous alcohol use and intimate partner violence (IPV)]. Furthermore, the analysis quantitatively examined the cumulative impact (defined as psychosocial burden) of these psychosocial risk factors on HIV treatment outcomes among young pregnant and postpartum WLHIV. Methods: This was a secondary data analysis of a pilot study (“Masibambisane Girls”) that designed and evaluated the role of a peer support intervention to mitigate the negative impact of stigma among young (16 – 24 years old) pregnant and postpartum WLHIV attending antenatal care (ANC) at the Gugulethu midwife obstetric unit (MOU), in Cape Town, South Africa. Participants were followed up to 6 months post enrolment. This analysis includes data collected from 114 of these pregnant (n=55) and postpartum (n=59) women. Psychosocial burden (primary exposure variable) was calculated as a sum score of the four key psychosocial risk factors. Each psychosocial risk factor threshold met scored the participant one point on psychosocial burden such that the minimum score was zero and the maximum was four. The prevalence of each exposure variable was analyzed using descriptive statistics and associations between them and with the outcome variables (engagement in care and HIV viral load <50 copies/mL) were examined using Chi2 tests and Fischer exact tests for sparse data. Poisson regression models were built to examine the association between psychosocial burden and HIV treatment outcomes before and after adjusting for sociodemographic and clinical confounding variables. Results: Overall, data from 114 women who were followed up for 6 months was analyzed (median age: 23 years, median gestation 25 weeks, median days postpartum: 6 days). There was an 88%, 14%, 19% and 32% prevalence of unintended pregnancy, probable depression, hazardous alcohol use and IPV respectively. Furthermore, probable depression and hazardous alcohol use were more prevalent among pregnant versus postpartum women. No statistically significant associations were found among these psychosocial risk factors. However, there was some indication of an association between depression and unintended pregnancy (P=0.095), depression and IPV (p=0.087) and hazardous alcohol use and IPV (p=0.119). The risk factors that most commonly co-occurred were unintended pregnancy and IPV (in 16% of women). Overall, pregnant women had significantly higher psychosocial burden scores than postpartum women. Analysis of HIV treatment outcomes revealed that 60% of women were engaged in care and among the 58 women who had an available viral load result within the window of follow up, 78% were virally suppressed. There was some indication of depression being a potential predictor of engagement in care (p=0.151). However, no statistically significant associations were found between any of the other psychosocial risk factors nor psychosocial burden scores and either HIV treatment outcome, before and after adjusting for potential confounders. Conclusions: This analysis mostly supports the existing body of literature on the prevalence of psychosocial risk factors and HIV treatment outcomes. However, more extensive research is needed to confirm associations among psychosocial risk factors and rigorously assess the cumulative impact of psychosocial risk factors (psychosocial burden) on HIV treatment outcomes.